Hacia un modelo de innovación de Gestión PUCP - Beaumont, Martín (2018)
A growing number of organizations and organizational practices around the world are incorporating criteria of justice and sustainability in their value proposition. With them, new meanings arise in the conceptual and analytic frameworks used in organizational studies. For example, Innovation and the systemic approach can be reconsidered in the context of value creation for society. This article reflects on how innovation can be understood by an undergraduate management school and its academic department (specifically at the Unidad de Gestión of the Pontifical Catholic University of Peru), and on how this understanding affects the purpose of the school itself, its academic model, and the relation with its environment.